GOLM1 is related to the inflammatory/immune nature of uveal melanoma and acts as a promising indicator for prognosis and immunotherapy response - Liang, Xin; Yin, Yu; Li, Ning (Frontiers in Genetics, 2022)
Purpose: Inflammatory/immune-related features are associated with the immunotherapy and prognosis of uveal melanoma (UVM). In this study, we systematically analyzed the correlation between GOLM1 and the inflammatory/immune nature of UVM and explored its potential value in predicting prognosis and guiding immunotherapy for UVM patients. Methods: A total of 143 UVM patients were enrolled in the current study. The differentially expressed genes between the GOLM1-low expression (LEXP) and GOLM1-high expression (HEXP) subgroups were calculated by the “limma” package and further annotated to reveal the key pathways by the “ClusterProfiler” package. Immunocyte infiltration was evaluated by single-sample gene set enrichment analysis, while the potential response to immunotherapy was realized by subclass mapping analysis. Moreover, tumor tissue sections from 23 UVM patients were collected and stained for GOLM1 (1:300; cat# DF8100, Affinity Biosciences), PD-L1 (1:250; cat# ab213524, Abcam), PD-1 (1:100; cat# ab52587, Abcam), CTLA-4 (1:300; cat# DF6793, Affinity Biosciences), and IFN-γ (1:300; cat# DF6045, Affinity Biosciences). Results: We found that higher expression of GOLM1 correlated with an unfavorable prognosis in UVM patients. Multivariate Cox regression analysis suggested that GOLM1 served as a prognostic factor independent of clinicopathological parameters. Notably, we found that the expression of PD-1, PD-L1, IFN-γ, and CTLA4 was higher in the GOLM1-high subgroup than in the GOLM1-low expression subgroup at the mRNA level and was subsequently validated at the protein level by immunohistochemistry. Gene pattern and SubMap analyses confirmed the indicator role of GOLM1 in predicting immunotherapy response in UVM. Conclusions: Taken together, GOLM1 is a novel prognostic marker, and it can be employed to predict the overall survival outcomes and treatment responses of anti-PD-1/PD-L1 and anti-CTLA4 therapies for UVM patients.